2012
DOI: 10.1103/physreva.85.042509
|View full text |Cite
|
Sign up to set email alerts
|

Self-energy calculation of the hydrogen atom: Importance of the unbound states

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Notably, the rationale for the SOSEX diagram as a cure for the self-screening problem of GW seems now justified if H is considered. This confirms early observations that the GW self-screening problem in H can be exacerbated by a starting point that suffers from a self-interaction/delocalization error and is instead small when an accurate starting point is adopted. , …”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Notably, the rationale for the SOSEX diagram as a cure for the self-screening problem of GW seems now justified if H is considered. This confirms early observations that the GW self-screening problem in H can be exacerbated by a starting point that suffers from a self-interaction/delocalization error and is instead small when an accurate starting point is adopted. , …”
Section: Resultssupporting
confidence: 87%
“…This confirms early observations that the GW self-screening problem in H can be exacerbated by a starting point that suffers from a self-interaction/delocalization error and is instead small when an accurate starting point is adopted. 50 , 51 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem was already documented in atomic calculations. For example, Sakuma and Aryasetiawan [39] have shown that in order to get the convergent total energy of the hydrogen atom (the simplest one!) in the GW approx imation, one has to sum up not only over bound states but also over an infinite number of the continuum states.…”
Section: Resultsmentioning
confidence: 99%